EFEKVITAS PENGGUNAAN APLIKASI MY PERTAMINA DI ERA KENAIKAN BBM BERSUBSIDI - Syamsir Syamsir; Ahmad Lutfi; Aulia Annisa Fitriani; Ira Ramadani; Nabilah Azahra Putri; Yurike Shizuka Nelsi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Fuel Oil (BBM) is one of the commodities from the natural resources of oil and natural gas. Oil and natural gas are non-renewable strategic natural resources controlled by country. Oil and natural gas have an important role in the national economy. So that the management of oil and natural gas must be able to provide optimally prosperity and welfare of society. The government made a policy regarding subsidized fuel in order to save on the state budget, and it is hoped that more people will use public transportation in order to reduce traffic jams in Indonesia. The government created the My Pertamina application to buy several Pertamina products such as fuel, but in its implementation this application reaped many pros and cons from the public.